Mobile government applications based on security and privacy: A literature review - Al-Sherideh A.S.; Ismail R.; Wahid F.A.; Ismail W.; Norasikin Fabil (Science Publishing Corporation Inc, 2024)
Indexed by SCOPUS/ERA